Police training and educational reforms within the colonial context of Puerto Rico - Perez, Xavier (Police and state crime in the Americas, 2024)
In 2011, the U.S. Department of Justice published a report investigating Puerto Rico’s Police Department (PRPD). The findings highlight that PRPD officers engage in a pattern of excessive use of force and civil rights violations. The lack of accountability is a product of insufficient training, little oversight, lack of procedures, and ineffectual management. The U.S. Department of Justice mandated PRPD to participate in a series of trainings to address human rights violations and inconsistent policing practices. The purpose of this study is to examine the impact of university-based training on police behavior and community relations. The study presents results from supervisory interviews and organizational surveys focused on police officers' ratings of in-service/post-academy training.